Nephroprotective Effect Of Clinacanhus Nutans, Orthosiphon Stamineus, And Syzyguim Camponulatum Leaves Against Cisplatin-Induced Nephrotoxcity; And Safety Asseement Of Clinacathus Nutans Leaves - Farsi, Elham (2017)
Cisplatin is an effective chemotherapeutic agent for solid tumors. However, it also induces dose-dependent progressive and irreversible nephrotoxicity. Cisplatin has multiple intracellular effects, which includes causing direct cytotoxicity with reactive oxygen species, activating apoptosis, and stimulating inflammation, events of which cause vascular and tubular dysfunction. Animal models have demonstrated that cisplatin-induced renal toxicity is characterized by a rapid loss of glomerular filtration, polyuria, hyperkalemia, hypernatremia, and azotemia. Recently, much attention has been given to the possible role of herbal medicine in protecting against cisplatin-induced renal toxicity.